EVALUATION OF ECONOMIC LIBERALIZATION POLICIES IN INCREASING FOREIGN DIRECT INVESTMENT IN SAUDI ARABIA (Case: Tourism Sector) - Amron, Syaukani; An-Najjar, Jamal (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
This study evaluates the economic liberalization policies implemented by Saudi Arabia in an effort to increase foreign direct investment (FDI) in the tourism sector, a sector that is a key focus in Vision 2030. Saudi Arabia, which has been dependent on the oil industry, has launched various reforms to diversify its economy and reduce its dependence on oil revenues. Through liberalization policies, including easing regulations, simplifying licensing, and providing incentives for foreign investors, the government seeks to attract more FDI to support the development of the tourism sector. This study analyzes the effectiveness of these policies using a case study approach and qualitative methods. The results of the analysis show that these policies have succeeded in attracting foreign investors, although there are still significant challenges, such as the perception of political and economic risks, as well as the need to improve infrastructure and the readiness of the local workforce. The findings of this study provide important insights for policymakers in developing further strategies to strengthen investment attractiveness in the tourism sector and ensure the success of sustainable economic diversification.